The Berenstain Bears and the messy room - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : Random House, 1983)
The entire Bear family becomes involved in an attempt to clean and organize the cubs' messy room.
3.7
K-3
Keywords: Bears -- Fiction; Cleanliness -- Fiction; Bears -- Fiction; Cleanliness -- Fiction